The effect of a 12-week functional training program on functional movement patterns and dynamic balance in young elite ice hockey players - Bieniec Anna; Grabara Małgorzata (Sciendo, 2024)
Study aim: This study examined the effects of a 12-week functional training (FT) program on basic movement patterns and dynamic balance in hockey players.